Wednesday

October 1, 2014

October 1, 2014

Posted by **Taylor** on Tuesday, July 22, 2014 at 10:29pm.

f(x)=1/3x-5

y=1/3x-5

x=1/3y-5

x-5=1/3y

y=the square root of x-5/3

- algebra 2 -
**Reiny**, Tuesday, July 22, 2014 at 11:28pmIs this supposed to be the solution to finding the inverse of

y = 1/3x - 5 ???

I suggest a 2-step process

1. interchange the x and y variables

----> x = 1/3y - 5

(you had that)

2. now solve this new equation for y

x = 1/3y - 5

x+5 = 1/3y

times 3

3x + 15 = y

so f^-1 (x) = 3x+15

Why did you involve a square root ??

**Answer this Question**

**Related Questions**

algebra - 1)Write the expression 9n^6+7n^3-6 in quadratic form,if possible A.9(n...

Algebra-One to one function - Could you please check my answers and help me with...

Algebra 2 - Ok, so I'm trying to find the inverse of each function. We're ...

Algebra - Rationalize each expression by building perfect nth root factors for ...

algebra - 1.)correct 2.)wrong---> the first term is wrong 4(3a^2)^2 = 36a^4 3...

Algebra - The function f(x)=x 3 +1 4 x−1 4 is a monotonically increasing ...

Pre Calculus - Inverse functions what is the inverse function of f(x)=1/square ...

math - Find the inverse of the function. f (x)=3 square root of 3x-3-4

Algebra(1st one was typo) - The function f(x)=x^3 +1/4 x −1^4 is a ...

Algebra - Use the quadratic formula to solve the equation. Give exact answers: ...